A neurocomputational model of visual selective attention for human computer interface applications - Neokleous, Kleanthis C.; Avraamides, Marios N.; Schizas, Christos N.; Neocleous, Costas (My University, 2011)
An overview of a neurocomputational model of visual selective attention that has been properly implemented is presented in this report. We briefly explain the basic components and neural interactions that comprise the model and we discuss its possible applications for human computer interaction.
Keywords: Spiking neural networks; Computational modeling; Visual selective attention